2018
DOI: 10.1101/334466
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BDNF controls cognitive processes related to neuropsychiatric manifestations via autophagic regulation of p62 and GABAA receptor trafficking

Abstract: Reduced BDNF and GABAergic inhibition co-occur in neuropsychiatric diseases, including major depression. Genetic rodent studies show a causal link, suggesting the presence of biological pathways that mediate this co-occurrence. Here we show that mice with reduced Bdnf (Bdnf +/-) have upregulated expression of sequestosome-1/p62, an autophagy-associated stress response protein, and reduced surface presentation of α5 subunit-containing GABA A receptor (α5-GABA A R) in prefrontal cortex (PFC) pyramidal neurons. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…It has been shown that the BDNF-TrkB system regulates GABAergic neurotransmission by different mechanisms, modulating expression (Bulleit et al, 2000;Roberts et al, 2006), phosphorylation (Vithlani et al, 2013) and trafficking (Brünig et al, 2001;Tomoda et al, 2022) of GABA A receptors, GABA release (Bardoni et al, 2007;Vaz et al, 2015), GABA transporter GAT-1 (Vaz et al, 2011), the function of the potassium-chloride co-transporter 2 (KCC2), which fine-tune intracellular chloride and the intensity of GABA A receptor currents (Dai et al, 2014) and the expression of the GABA-synthesizing enzyme GAD67 (Arenas et al, 1996).…”
Section: Tnfα-tnfr1-s1pr2-ccl2-bdnf-trkb Pathwaymentioning
confidence: 99%
“…It has been shown that the BDNF-TrkB system regulates GABAergic neurotransmission by different mechanisms, modulating expression (Bulleit et al, 2000;Roberts et al, 2006), phosphorylation (Vithlani et al, 2013) and trafficking (Brünig et al, 2001;Tomoda et al, 2022) of GABA A receptors, GABA release (Bardoni et al, 2007;Vaz et al, 2015), GABA transporter GAT-1 (Vaz et al, 2011), the function of the potassium-chloride co-transporter 2 (KCC2), which fine-tune intracellular chloride and the intensity of GABA A receptor currents (Dai et al, 2014) and the expression of the GABA-synthesizing enzyme GAD67 (Arenas et al, 1996).…”
Section: Tnfα-tnfr1-s1pr2-ccl2-bdnf-trkb Pathwaymentioning
confidence: 99%
“…To visualize dendritic and spine morphology of major output neurons in culture, we prepared primary cortical neurons (61)…”
Section: Primary Cortical Neurons In Culture and Morphometric Analysismentioning
confidence: 99%